Hubungan Antara Kelainan Refraksi Dengan Perilaku Membaca Pada Siswa Anggota Jemaat Gereja Kristen Nafiri Sion Fajar Kemuliaan Tahun 2023 - Indrajanti, Mirza; Wijaya, Esther; Nila, Seri; Sinaga, Natasya Advelin; Gosali, Vincentio Owen; Kencana, Billy Gadi (Jurnal MedScientiae, 2024)
Myopia is an eye disorder in which parallel rays coming from an infinite distance are refracted in front of the retina. Astigmatism is an optical condition of the eye, in which parallel rays are not refracted at a single focal point, so that the focus is unclear, vision is blurred and often dizzy. Anisometropia is a difference in refractive error between the two eyes of 1-2 Diopters (D) in one or more meridians. This can cause aniseikonia, namely a difference in shadow both in shape and size that causes difficulty in fusion. Hypermetropia / Hyperopia / farsightedness is a condition of not being able to see close objects clearly, this condition is the opposite of farsightedness (myopia). The symptoms of hypermetropia are similar to presbyopia in the elderly. Research objective is to educate students about visual health. Method is data collection was conducted through anamnesis, visual acuity examination using refraction instruments and distributing questionnaires to students of the Nafiri Sion Fajar Kemuliaan Christian Church aged 12-22 years, totaling 62 people, then diagnosed with refractive disorders. There is a relationship between refractive disorders and students' reading behavior.